Gender Identity in Mahesh Dattani’s Tara: Challenging Gender Stereotypes in Indian Society (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Mahesh Dattani a noted Indian playwright, tries to shatter the stereotypical representations of woman in his plays. He is able to see beyond the accepted institutions and beliefs of the conventional society. The paper tries to present how the playwright, in his play Tara has portrayed dexterously the pathetic struggle a woman undergoes in her life. Women are marginalized and are at the receiving end of the oppressive structures. The reason behind is the gender politics. Women fail to voice their opinions or represent leadership in all walks of life. So, the play exposes an average Indian mindset in the present times.